1999
DOI: 10.1038/sj.ijo.0800972
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the cholesteryl ester transfer protein gene TaqIB polymorphism to the reduced plasma HDL-cholesterol levels found in abdominal obese men with the features of the insulin resistance syndrome

Abstract: OBJECTIVE: The aim of this study was to examine the relation between the CETP-TaqIB polymorphism and reduced plasma HDL-cholesterol levels commonly observed among men characterized by abdominal obesity and features of the insulin resistance syndrome. SUBJECTS: A total of 187 sedentary men, non-smokers and free from metabolic disorders were classi®ed on the basis of their CETP-TaqIB genotype. RESULTS: Plasma HDL and HDL 3 -cholesterol concentrations as well as the CETP activity were signi®cantly different betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 14 publications
1
35
2
2
Order By: Relevance
“…In addition to smoking and male sex, obesity, visceral fat accumulation, and hyperinsulinemia have also been reported to blunt the effect of TaqIB genotype on HDL-C levels. 13,14 In the present analysis, we were only able to study an interaction with BMI, which we did not detect. Given the fact that the interactions described in the literature were of greater magnitude than the detectable effect size shown in Table 4, we conclude that an interaction between TaqIB genotype and BMI is unlikely.…”
Section: Effect Modification By Environmental Factorsmentioning
confidence: 59%
See 2 more Smart Citations
“…In addition to smoking and male sex, obesity, visceral fat accumulation, and hyperinsulinemia have also been reported to blunt the effect of TaqIB genotype on HDL-C levels. 13,14 In the present analysis, we were only able to study an interaction with BMI, which we did not detect. Given the fact that the interactions described in the literature were of greater magnitude than the detectable effect size shown in Table 4, we conclude that an interaction between TaqIB genotype and BMI is unlikely.…”
Section: Effect Modification By Environmental Factorsmentioning
confidence: 59%
“…We investigated whether our pooled dataset provided any evidence for the published interactions between TaqIB genotype and sex, 11,12 smoking, 8,13 BMI, 13,14 and use of alcohol. 15 The present meta-analysis provides some evidence that interactions exist for both sex and smoking (Pϭ0.02 for each), such that the effect of TaqIB genotype on HDL-C levels was attenuated among men and among smokers.…”
Section: Effect Modification By Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is concordant with our earlier studies. [37][38][39][40] Our results specifically illustrate that combinations of genetic factors sequentially involved in the VLDL catabolic pathway might influence the expression of the 'hypertriglyceridemic-waist' phenotype. Prevention of the risk associated with the 'hypertriglyceridemic-waist' phenotype importantly relies on intervention on life habits (diet, physical activity, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported no relationship between the TaqIB polymorphism and HDL-C levels in T2DM patients (29,30) while Kawasaki observed conversely. Several factors are involved in this relationship including gender, smoking and body mass index (BMI) (31,32). Considering the key role of CETP in the metabolism of lipoproteins, different polymorphisms in the CETP gene may affect blood lipid parameters.…”
mentioning
confidence: 99%